2020
DOI: 10.1001/jama.2020.14984
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence Testing of Residents for SARS-CoV-2 in a Subset of Connecticut Nursing Homes

Abstract: The first case of coronavirus disease 2019 (COVID-19) in Connecticut was reported in a nursing home (NH) on March 15, 2020. Within the next 2 months, 80.0% of Connecticut's 215 NHs reported at least 1 case of COVID-19, accounting for 61.6% of COVID-19 deaths in the state. 1 Residents were initially tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) only if symptomatic, as per recommendations from the Centers for Disease Control and Prevention. In early May, NHs were prioritized and selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 4 publications
1
18
1
Order By: Relevance
“…26 Testing asymptomatic people is crucial to preventing outbreaks, since recent reports have shown that up to 88% of infected people do not have any symptoms at the time of testing. 27 Novel methods of testing, and their potential to improve epidemic tracking and to relieve supply chain pressure should be further explored. 13,28,29 Controlling COVID-19 outbreaks is possible, as evidenced by the pandemic responses in, among others, South Korea, Vietnam, Germany, and New Zealand, 30,31 and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…26 Testing asymptomatic people is crucial to preventing outbreaks, since recent reports have shown that up to 88% of infected people do not have any symptoms at the time of testing. 27 Novel methods of testing, and their potential to improve epidemic tracking and to relieve supply chain pressure should be further explored. 13,28,29 Controlling COVID-19 outbreaks is possible, as evidenced by the pandemic responses in, among others, South Korea, Vietnam, Germany, and New Zealand, 30,31 and necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the data presented in other studies [27][28][29][30][31][32][33][34][35] conducted in nursing homes for elderly people, we would have expected a significantly higher number of cases, and consequently, a higher number of deaths.…”
Section: Integrationmentioning
confidence: 93%
“…In the midst of the coronavirus disease (COVID-19) pandemic, nursing homes account for a substantial proportion of total deaths attributed to the virus in the United States and globally ( 1 3 ). The high proportion of asymptomatic, presymptomatic, and atypical manifestations of COVID-19 in staff and elderly residents is a critical driver of widespread and rapid transmission of the virus ( 4 6 ). Facilitywide testing is a critical tool to identify such infections, particularly in lieu of effective vaccines or treatments early in a novel viral outbreak ( 7 10 ).…”
mentioning
confidence: 99%
“…The first COVID-19 case was reported in a nursing home in Connecticut on March 15, 2020. Over the next 2 months, nursing homes accounted for 61.6% deaths in the state ( 6 ). After an increase in testing resources and evidence of asymptomatic transmission, the Connecticut Department of Public Health (CT DPH) began PPS testing in early May, and PPS testing was formally recommended on May 11 and mandated weekly in staff effective June 14 ( 11 , 12 ).…”
mentioning
confidence: 99%